Problems of Cartesian Product Solved by Elementary School Students Sandra Maria Pinto MaginaI - Sandra Maria Pinto Magina; Alina Galvão Spinillo; Lianny Milenna de Sá Melo (Universidade Federal do Rio Grande do Sul, 2018)
The study investigated the solution of direct (which requires multiplication for its resolution) and inverse (which requires division for its resolution) Cartesian product problems by elementary education students, examining the level of problem complexity and the children procedures according to the type of problem. A total of 269 8 and 10 year-old students attending from 3rd to 5th grade, were asked 8 and 10 years to solve direct and inverse Cartesian product problems. As expected, the inverse problem was the most difficult one. The strategies showed that levels of combinatorial reasoning vary according to the type of problem. It was also found a progression in the solution of direct Cartesian product problems, but not in relation to the solution of inverse problems.